2015
DOI: 10.1590/1414-431x20144212
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ induces growth inhibition and apoptosis through upregulation of insulin-like growth factor-binding protein-3 in gastric cancer cells

Abstract: Peroxisome proliferator activator receptor-gamma (PPARγ) is a ligand-activated transcriptional factor involved in the carcinogenesis of various cancers. Insulin-like growth factor-binding protein-3 (IGFBP-3) is a tumor suppressor gene that has anti-apoptotic activity. The purpose of this study was to investigate the anticancer mechanism of PPARγ with respect to IGFBP-3. PPARγ was overexpressed in SNU-668 gastric cancer cells using an adenovirus gene transfer system. The cells in which PPARγ was overexpressed e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…Insulin like growth factor binding protein-3 (IGFBP3), the most abundant of the six IGFBPs (Shahjee et al, 2013), is a key mediator of insulin-like growth factor (IGF) biological activity (Firth & Baxter, 2002). Several studies have shown that IGFBP3 could regulate cell proliferation by inducing its anti-proliferative and pro-apoptotic effects in different types of cancer cells (Han et al, 2014;Kim et al, 2015;Shahjee & Bhattacharyya, 2014). However, the IGFBP3 effects on the normal cell were relatively unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Insulin like growth factor binding protein-3 (IGFBP3), the most abundant of the six IGFBPs (Shahjee et al, 2013), is a key mediator of insulin-like growth factor (IGF) biological activity (Firth & Baxter, 2002). Several studies have shown that IGFBP3 could regulate cell proliferation by inducing its anti-proliferative and pro-apoptotic effects in different types of cancer cells (Han et al, 2014;Kim et al, 2015;Shahjee & Bhattacharyya, 2014). However, the IGFBP3 effects on the normal cell were relatively unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Also, transactivation of PPARγ lowers the level of angiogenic factors and reduces the migration and proliferation of endothelial cells [249]. The overexpression of PPARγ receptors in SNU-668 gastric cancer cells having adenovirus gene exhibited significant growth inhibition and activation of apoptosis due to strong up-regulation of a tumor suppressor gene, insulin-like growth factor-binding protein-3 [250]. Some workers have shown that the genomic activation of PPARγ by microRNA-125b suppress the expression of B-cell lymphoma 3 protein, a proto-oncogene, thereby reduce the growth of ovarian cancer [251].…”
Section: Mechanism Of Antitumor Action By Tzdsmentioning
confidence: 99%
“…Adenovirus gene transferred SNU-668 gastric cancer cells with overexpression of PPARγ presented significant the growth inhibition and apoptosis activation due to strong IGFBP-3 upregulation. Insulin-like growth factor-binding protein-3 IGFBP-3 is a tumor suppressor gene, independent of IGF signaling [ 76 ]. Some reports proved that activation of PPARγ can inhibit the growth of ovarian cancer by suppressing proto-oncogene B-cell lymphoma 3-encoded protein (BCL3) in response to microRNA-125b (miR-125b) tumor suppressor upregulation.…”
Section: Molecular Polymorphism and Function Of Pparmentioning
confidence: 99%